Genotypic and phenotypic mechanisms underlying antimicrobial resistance and synergistic efficacy of rifampicin-based combinations against carbapenem-resistant Acinetobacter baumannii - Lois Chinwe Nwabor; Arnon Chukamnerd; Ozioma Forstinus Nwabor; Komwit Surachat; Rattanaruji Pomwised; Kongpop Jeenkeawpiam; Sarunyou Chusri (Heliyon, 2024)
Purpose: Carbapenem-resistant Acinetobacter baumannii (CRAB) is an urgent concern to public health. This study focuses on exploring the resistance mechanisms and the in vitro results of using rifampicin in combination with conventional antibiotics for the management of CRAB. Methods: The synergistic and bactericidal effects of rifampicin with conventional antibiotics were evaluated using chequerboard assay and time-kill assay, while the phenotypic and genotypic characteristics of resistant determinants were performed by efflux pump detection and whole genome sequencing on 29 isolates from ICU patients with underlying health diseases. Results: The isolates showed multidrug resistance, with over 60% showing addictive responses to rifampicin-based combinations at FICI ranging from 0.6 to 0.8. The time-kill assay revealed 99 % killing for rifampicin and minocycline combination in one isolate at 1/4 MIC rifampicin plus 1/4 MIC minocycline, while a bacteriostatic effect was observed at 1/2 MIC rifampici plus 1/2 MIC for a second isolate. Combination with tigecycline resulted in a 99% killing in two out of three isolates with a 2.5–3 log reduction in CFU at 1/4 MIC rifampicin plus 1/4 MIC tigecycline. Rifampicin plus colistin exhibited bactericidal activity against three out of four isolates. The combinations of rifampicin with ciprofloxacin, chloramphenicol, and trimethoprim-sulfamethoxazole were ineffective against the isolates. In addition, a 4-fold reduction in rifampicin MIC was observed in 2 out of 14 isolates in the presence of an efflux pump inhibitor. The pan-genome study demonstrated a progressive evolution with an accessory genome estimated to cover 58% of the matrix. Seven of the ten sequenced isolates belong to sequence type 2 (ST2), while one isolate each was assigned to ST164, ST16, and ST25. Furthermore, 11 plasmids, 34 antimicrobial resistance (AMR) genes, and 65 virulence-associated genes were predicted from the whole genome data. The blaOXA-23 blaADC-25, blaOXA-66, blaPER-7, aph(6)-Id, armA, and arr-3 were prevalent among the isolates. Sequence alignment of the bacteria genome to the reference strain revealed a deleterious mutation in the rpoB gene of 4 isolates. Conclusion: The study suggests that rifampicin in combination with either minocycline, tigecycline, or colistin might be a treatment option for CRAB clinical isolates. In addition, genotypic analysis of the bacteria isolates may inform the clinician of the suitable drug regimen for the management of specific bacteria variants.